2011
DOI: 10.1007/s10916-011-9672-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Web 2.0 Diabetes Care Support System with Evaluation from Care Provider Perspectives

Abstract: Diabetes is a life-long illness condition that many diabetic patients end up with related complications resulted largely from lacking of proper supports. The success of diabetes care relies mainly on patient's daily self-care activities and care providers' continuous support. However, the self-care activities are socially bounded with patient's everyday schedules that can easily be forgotten or neglected and the care support from providers has yet been fully implemented. This study develops a Web 2.0 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
(62 reference statements)
0
14
0
1
Order By: Relevance
“…Lin et al [13] have developed a Web 2.0 based diabetes support system with care provider perspectives. The system supports care managers in a health service center to conduct patient management through collecting patients daily physiological information, sharing care information, and maintaining patient-provider relationships.…”
Section: Related Research In Persuasive Healthcarementioning
confidence: 99%
“…Lin et al [13] have developed a Web 2.0 based diabetes support system with care provider perspectives. The system supports care managers in a health service center to conduct patient management through collecting patients daily physiological information, sharing care information, and maintaining patient-provider relationships.…”
Section: Related Research In Persuasive Healthcarementioning
confidence: 99%
“…Moreover, reviews have shown that the effects of CHITs on patient outcomes have been mixed [5][6][7][8][9]; therefore, further study is needed to evaluate the effects. In addition, many recent CHIT applications are based on advanced information and communication technologies in general or mobile technologies in particular (e.g., smartphones and tablet computers) due to their low cost, high portability, high accessibility, and ease of implementation [10][11][12]. To this end, our research team developed a tablet-based self-monitoring system according to human factors design methods and principles in an attempt to make the system usable and useful [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The effectiveness of telehealthcare service has been indicated, [12][13][14][15][16] and there have been many related works in the past decades, such as hypertension, diabetes, heart disease after surgery, or pediatric care. 8,10,12,[17][18][19][20][21][22][23][24] Some of the research has focused on individual diseases, [25][26][27][28][29][30][31] and some has supported generalized chronic disease care. 5,32 Information technology (IT) is increasingly used in healthcare practice, and IT infrastructure appears to be essential while providing telehealthcare service.…”
Section: Introductionmentioning
confidence: 99%
“…5,32 Information technology (IT) is increasingly used in healthcare practice, and IT infrastructure appears to be essential while providing telehealthcare service. There are many designs of telehealthcare systems, 5,[25][26][27][28][29][30][31][32][33] mostly adopting Web-based architecture 5,[25][26][27]29,30,33 to ensure portability. Some have adopted medical informatics standards 5,27,29 to retain interoperability, and some have exchanged data with existed information systems through an nonstandardized approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation